DESCRIPTION DUN NOUVEAU GENRE DE PLEUROGENETINAE TREMATODA LECITHODENDRIIDAE DES GRENOUILLES DU MEXIQUE LANGERONIA MACROCIRRA N G N SAN LUIS POTOSI - HOLLIS BRAVO, M; CABALLERO Y C, EDUARDO; C (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
A new alum-precipitated bacterin against brucellosis was tested to determine the protection or immunity in mice, guinea pigs and rabbits Mice inoculated with 1 or 2 bacterin doses showed some protection against variable doses of Brucella In vaccinated g
ANN PHYS N Y
Keywords: DESCRIPTION, NOUVEAU GENRE, PLEUROGENETINAE, TREMATODA: LECITHODENDRIIDAE , GRENOUILLES, MEXIQUE LANGERONIA MACROCIRRA N G N SP; CIENCIAS DE LA VIDA; MICROBIOLOGIA; BACTERIOLOGIA